Rare Presentation of Adult‐Onset Still's Disease Complicated by Acute Severe Hepatitis Refractory to Medical Treatment: A Case Report - Majed Ali; Karam Karam; Emanuel‐Youssef Dib; Elias Fiani (Clinical Case Reports, 2025)
ABSTRACT Managing adult‐onset Still's disease complicated by severe hepatitis requires vigilant monitoring and adaptable therapeutic strategies. Standard treatments such as tocilizumab and rituximab can cause adverse reactions or lose efficacy. The interplay of systemic inflammation and liver involvement highlights the need for ongoing research to find effective, safe treatment alternatives.